Assessing The Regulation of Tiktok Shop by The Minister of Trade Through Maqashid Syariah - Rifky Pratama, Muhammad; Piracha, Fatimah (Mu’amalah: Jurnal Hukum Ekonomi Syariah, 2024)
Integrating social media platforms in commercial activities introduces complex challenges, particularly in consumer protection, economic justice, and alignment with ethical and legal standards. This study aims to analyze the Minister of Trade’s regulation on TikTok Shop through the lens of Maqashid Syariah to assess its compatibility with Islamic moral values and legal principles. Adopting a qualitative research methodology utilizes a formal literature review and content analysis to examine the relevant provisions of the regulation. The findings indicate that current laws governing online commerce require further adaptation to better align with the principles of Maqashid Syariah, ensuring fairness, sustainability, and societal welfare in digital transactions. This research contributes to the ongoing discourse on strengthening the regulatory framework for online commerce, promoting ethical standards, and fostering a more equitable and sustainable business environment. The study also offers a foundation for policy development that supports the growth of online commerce in a manner that benefits all stakeholders while adhering to Islamic principles of justice and public welfare.